2020
DOI: 10.3390/ijms21217881
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Roles of the Receptor-Like Kinase Feronia in Plant Growth, Development and Host-Pathogen Interaction

Abstract: As a member of the Catharanthus roseus receptor-like kinase 1-like (CrRLK1L) protein kinase subfamily, FERONIA (FER) has emerged as a versatile player regulating multifaceted functions in growth and development, as well as responses to environmental factors and pathogens. With the concerted efforts of researchers, the molecular mechanism underlying FER-dependent signaling has been gradually elucidated. A number of cellular processes regulated by FER-ligand interactions have been extensively reported, implying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 88 publications
0
26
0
Order By: Relevance
“…Cr RLK1Ls display exquisite versatility in mediating responses to multiple phytohormones and stresses, which we describe briefly here (widely reviewed by Franck et al ., 2018a,b; Liao et al ., 2017; Zhang et al ., 2020b; Ji et al ., 2020a).…”
Section: Crrlk1l‐mediated Regulation Of Phytohormone and Stress Respo...mentioning
confidence: 99%
“…Cr RLK1Ls display exquisite versatility in mediating responses to multiple phytohormones and stresses, which we describe briefly here (widely reviewed by Franck et al ., 2018a,b; Liao et al ., 2017; Zhang et al ., 2020b; Ji et al ., 2020a).…”
Section: Crrlk1l‐mediated Regulation Of Phytohormone and Stress Respo...mentioning
confidence: 99%
“…The activation of this type of channel is associated with the functioning of the receptor-like kinase FERONIA (FER) and the peptide hormone RALF (rapid alkalinization factor), which is confirmed by the Ca 2+ -wave suppression by neomycin [ 148 ] and in FER-deficient Arabidopsis plants [ 138 ]. Mechanical stimulus can facilitate RALF–FER interactions by inducing RALF secretion or increasing the availability of FER binding surfaces for the peptide [ 138 , 149 ].…”
Section: Stimulus Perceptionmentioning
confidence: 99%
“…More importantly, the latest findings demonstrate that FER functions by preventing the approach and penetration of late-arriving pollen tubes by triggering the accumulation of nitric oxide at the filiform apparatus upon the arrival of the first female gametophyte at the ovule [ 11 ]. After nearly two decades of research effort, FER has been found to play critical roles in cell growth, reproduction, plant morphogenesis, immunity, hormone signaling, and stress responses [ 1 , 5 , 14 , 15 , 16 ], suggesting its key roles in plant growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…Phytohormones are involved in nearly all aspects of the plant life cycle, ranging from seed germination, growth and development, flowering, and fruit ripening, to immunity by integrating endogenous signals and extra-environmental cues. As a critical receptor kinase, FER is involved in many hormonal signaling pathways that regulate plant growth, development, and immunity [ 2 , 14 , 15 ]. Here, we focus on the recent findings related to the functions of FER in hormone signaling pathways and summarize them by different types of phytohormones.…”
Section: Introductionmentioning
confidence: 99%